Ядерная ДНК-топоизомераза зародышей кукурузы - Карпенчук, К.Г.; Руденко, Г.Н. (Биополимеры и клетка, 1987)
Из ядерного экстракта зрелых зародышей Zea mays выделена и частично очищена АТР-независимая ДНК-топоизомераза предположительно I типа. Релаксация отрицательно суперспирализованной ДНК плазмиды pBR322 не ингибируется ЭДТА, новобиоцином и налидиксовой кислотой, активируется ионами магния и полиаминами (спермидином и кадаверином), ингибируется SH-специфическими реагентами и ауринтрикарбоновой кислотой. З ядерного екстракту зрілих зародків Zea mays виділено і частково очищено АТР-незалежну ДНК-топоізомеразу, імовірно, I типу. Релаксацію негативно суперспіралізованої ДНК плазміди pBR322 не інгібують ЕДТА, новобіоцин і налідиксова кислота, активують іони магнію і поліамін (спермідин і кадаверин), пригнічують SH-специфічні реагенти та ауринтрикарбонова кислота. ATP-independent presumably type I DNA topoisomerase was partially purified from the nuclear extract of Zea mays mature embryos by separation in the polyethylene glycol-ammonium sulphate system with 2 M NaCl and by salt gradient elution from CM-Sepha-dex. The ability of enzyme to relax negative supercoils of plasmid pBR322 DNA was detected in the presence of EDTA, being however markedly stimulated by the magnesium ions and polyamines (spermidine and cadaverine). The reaction proceeded via either processive or distributive mechanism depending on the ionic strength of the enzyme assay mixture. Novobiocin and nalidixic acid (both at 100 u.g/ml) did not inhibit the enzyme activity. Modification with p-hydroxymercuribenzoate or iodoacetamide completely abolished the DNA topoisomerase activity, thus indicating the presence of essential cysteine residues in the enzyme molecules. The DNA topoisomerase activity was found to be completely depressed by the preparation of potent inhibitor of polynucleotide-binding proteins – aurintricarboxylic acid in partially polymerized form. Magnesium ions partially restored the DNA topoisomerase activity in the presence of aurintricarboxylic acid.